Kepemimpinan Kepala Madrasah dalam Konteks Manajemen Berbasis Sekolah (MBS) pada MAN 13 Jakarta - Maman Saepulloh (Jurnal Dirosah Islamiyah, 2024)
This study aims to explore and analyze the role of school leadership in the implementation of School-Based Management (SBM) at MAN 13 Jakarta. In the era of educational decentralization, SBM is a model applied to improve educational quality through increased participation and accountability at the school level. The research method used is a qualitative approach with in-depth interviews, observations, and document analysis. The findings reveal that leadership at MAN 13 Jakarta plays a crucial role in mobilizing the participation of all stakeholders, including teachers, students, and parents, as well as in creating a conducive learning environment. Effective leadership at MAN 13 Jakarta is characterized by open communication, transparency in decision-making, and staff empowerment. Challenges faced include resistance to change and resource limitations, but these can be overcome through adaptive and collaborative leadership strategies.